Implementation of Halal Product Guarantee Throught Halal Certification on Cosmetic Products in Indonesia - Dwi Nabilah Nur Utari; Nuril Khikmatus Tsuroyyah (Universitas Negeri Surabaya, 2024)
The halal industry is a key pillar of the global economy. The demand for halal products continues to increase, especially in countries such as Indonesia, which has the largest Muslim population. This study uses a descriptive qualitative research type by analyzing the implementation of halal certification in the Indonesian cosmetics industry, focusing on its challenges and opportunities. Halal certification, which is regulated by the Halal Product Guarantee Agency (BPJPH) under Law No. 33 of 2014, ensures that products comply with Islamic law. The results of this study show that although halal certification is beneficial in increasing consumer confidence and market competitiveness, there are still some challenges in its implementation such as high certification costs, complicated processes, and limited awareness. This study highlights the importance of continued support from regulatory bodies to overcome these barriers and maintain halal standards.